1996
DOI: 10.1111/j.1540-8159.1996.tb03264.x
|View full text |Cite
|
Sign up to set email alerts
|

Shortcut Link Between the Fast and Slow Pathways and the Mechanism of Cure in Atrioventricular Nodal Reentrant Tachycardia by Catheter Ablation

Abstract: In patients with a shortcut link between the fast and slow pathways, slow pathway conduction itself does not need to be impaired to eliminate the AVNRT, whereas in patients without this shortcut link, slow pathway conduction must be impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…reported that observation of orthodromic capture of the atrial electrogram at the atrial EAS by CS pacing could rule out the presence of a UCP in AVNRT 3 . Another explanation of VAB during AVNRT is a shortcut link connecting the dual nodal pathways, reported by Nogami et al 4 . In the presence of a shortcut link, we could explain the mechanism of the VAB during the tachycardia as follows (Figure 2).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…reported that observation of orthodromic capture of the atrial electrogram at the atrial EAS by CS pacing could rule out the presence of a UCP in AVNRT 3 . Another explanation of VAB during AVNRT is a shortcut link connecting the dual nodal pathways, reported by Nogami et al 4 . In the presence of a shortcut link, we could explain the mechanism of the VAB during the tachycardia as follows (Figure 2).…”
Section: Discussionmentioning
confidence: 68%
“…This ruled out atrial tachycardia and orthodromic atrioventricular reentrant tachycardia (ORT) using rule out the presence of a UCP in AVNRT. 3 Another explanation of VAB during AVNRT is a shortcut link connecting the dual nodal pathways, reported by Nogami et al 4 In the presence of a shortcut link, we could explain the mechanism of the VAB during the tachycardia as follows (Figure 2). The AVNRT had dual loop circuits, one circuit contained the atrial myocardium and in the other circuit, the antegrade slow pathway and retrograde slow pathway were connected by a shortcut link.…”
Section: Discussionmentioning
confidence: 76%
“…Following curative surgical treatment,^'^ catheter ablation for AV nodal reentrant tachycardia was introduced in 1986 using DC shocks applied to the retrograde fast pathway, a few millimeters from the His hunjjlg 24.2.5 purther attempts to consistently ablate the "guilty" retrograde fast pathway without modifying anterograde conduction have been unsuccessful so that the risk of AV block targeting the fast pathway remains about 3% with the use of radiofrequency (RF) current.^'*"^'^ This risk is greater than using RF ahlation to target the "slow pathway" (SP) in which energy is applied 10-20 mm posterior to the His bundle with an incidence =1% of AV hlock. This approach Introduced by Jackman et al^° has become the therapeutic procedure of choice.^""""^^ Although ablation for AVJRT is dichotomized into fast or slow pathway ablation, there are arguments suggesting disruption of the link between botb pathways (or of an "intermediate" pathway) as the mechanism of ,U^,g 46,48,49 Different approaches to target the slow pathway have heen described. In the electrophysiological approach, electrogram patterns are nsed to identify the ablation site^"*^^ whereas in the anatomical approach, the ablation site is mainly selected on the basis of anatomical criteria (in combination with an atrial/ventricular electrogram ratio of 0.5 or less).…”
Section: Catheter Ablation Of Avjrt: Anatomical Ormentioning
confidence: 99%